Impact of Soil Health Card Scheme on Soil Fertility and Crop Production Among the Adopted Farmers - Singh, B. P.; Kumar, Vijay; Chander, Mahesh; Reddy, M. B.; Shruti,; Singh, Madan; Suman, R. S.; Yadav, Vanee (Indian Journal of Extension Education, 2022)
The study was conducted in Bareilly district of western UP regarding adoption of recommendation of soil health card scheme and its impact on productivity and economics of different crops i.e. wheat, paddy and sugarcane. It was found that only 40 per cent farmers owned soil health card. However, due to adoption of SHT based fertilizer recommendations there was a significant increase in crop yields of wheat (30.80%), paddy (29.80%) and sugarcane (32.90%). In addition, the adoption of SHT based fertilizer recommendation had a significant reduction in production cost by Rs. 2130, 2164 and 3122/- per acre of wheat, paddy and sugarcane crops, respectively. Also, the net increase in farmer’s income was realised from one acre of wheat, paddy and sugarcane was about Rs. 11197, 12058 & 29187, respectively. Thus, the application of SHT under field condition has reduced the production cost and increased the farmers’ income.
Keywords: Adopted farmers; Crop production; Soil fertility; Soil health card scheme